A Cross-Sectional Analysis of Employment Returns to Education and Health Status in China: Moderating Role of Gender - Yahong, Wang; Khan, Salim (Frontiers in Psychology, 2021)
Based on nationally representative sample data from the Chinese General Social Survey (CGSS-2015), this study examines the relationship of education levels and health status with an individual’s probability of being employed in China. The findings obtained from the binary logistic regression estimator suggest that people with a higher level of education were more likely to be employed than those who have less or no education. The individual with university or above education was found to be 85% more likely to be employed than college or equal diploma holders. Further, the healthier individual was found to be 11% more likely to be employed than relatively less healthy. Moreover, the resulted coefficients obtained from the moderation effect suggest that all of the two-way interaction effects among health status and education levels with gender are not statistically significant even at the 10% level. The results suggest that there was no multiplicative effect of gender with health status and level of education on an individual’s probability of being employed. Further, the study also suggests important policy implications in the light of China’s active labor force market and the gender gap in employment.